2004
DOI: 10.1182/blood-2004-03-0890
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of a humanized anti-CD74 monoclonal antibody, hLL1, on B-cell malignancies

Abstract: The humanized anti-CD74 monoclonal antibody (mAb) hLL1 is under evaluation as a therapeutic agent. The effects of hLL1-at times in comparison with the CD20 mAb rituximab-were assessed on non-Hodgkin lymphoma (NHL) and multiple myeloma (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
113
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 31 publications
(44 reference statements)
8
113
0
Order By: Relevance
“…Fab' internalization occurs just as rapidly as immunoglobulin G (IgG) binding, indicating that bivalent binding is not required (3,10). Later studies with a complementarity-determining region (CDR)-grafted version of murine LL1, milatuzumab (hLL1), found that the antibody could alter B-cell proliferation, migration, and adhesion molecule expression (8,11,12), but the exceptional internalization properties of the anti-CD74 antibody made it an efficient carrier for the intracellular delivery of cancer therapeutics (13)(14)(15)(16). On the basis of preclinical efficacy and toxicology results, phase I clinical trials with milatuzumab in multiple myeloma (17), as well as milatuzumab-doxorubicin in multiple myeloma, non-Hodgkin lymphoma, and chronic lymphocytic leukemia, have been initiated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fab' internalization occurs just as rapidly as immunoglobulin G (IgG) binding, indicating that bivalent binding is not required (3,10). Later studies with a complementarity-determining region (CDR)-grafted version of murine LL1, milatuzumab (hLL1), found that the antibody could alter B-cell proliferation, migration, and adhesion molecule expression (8,11,12), but the exceptional internalization properties of the anti-CD74 antibody made it an efficient carrier for the intracellular delivery of cancer therapeutics (13)(14)(15)(16). On the basis of preclinical efficacy and toxicology results, phase I clinical trials with milatuzumab in multiple myeloma (17), as well as milatuzumab-doxorubicin in multiple myeloma, non-Hodgkin lymphoma, and chronic lymphocytic leukemia, have been initiated.…”
Section: Introductionmentioning
confidence: 99%
“…In normal human tissues, CD74 is primarily expressed in B cells, monocytes, macrophages, dendritic cells, Langerhans cells, subsets of activated T cells, and thymic epithelium (data on file; Immunomedics, Inc.), and it is expressed in more than 90% of B-cell tumors (7,8). Early studies had conflicting data on whether CD74 is present on the membrane, in part because the antibodies to the invariant chain were specific for the cytoplasmic portion of the molecule (9), but also because there are relatively few copies on the surface, and its half-life on the cell surface is very short.…”
Section: Introductionmentioning
confidence: 99%
“…86 In a myeloma mouse model, treatment with milatuzumab resulted in significant survival extensions without the need for an exogenous crosslinking agent. 85,86 Doxorubicin conjugated to this antibody (IMMU-110) had cytotoxic effects on myeloma cells in vitro and inhibited tumor growth in a mouse model without significant toxicity. 87 Also the immunotoxin, 2L-Rap-hLL1-g4P, composed of frog RNase fused to the anti-CD74 antibody killed myeloma cells in vitro.…”
Section: Cd74mentioning
confidence: 99%
“…84 Crosslinked milatuzumab (hLL1, IMMU-115), a humanized anti-CD74 mAb, blocks CD74 and thereby prevents NF-kB activation, resulting in growth-inhibitory effects and induction of apoptosis in myeloma cell lines. 85,86 Milatuzumab lacks CDC or ADCC activity. 86 In a myeloma mouse model, treatment with milatuzumab resulted in significant survival extensions without the need for an exogenous crosslinking agent.…”
Section: Cd74mentioning
confidence: 99%
See 1 more Smart Citation